Role of chitosan in enhancing Raman signal and improving uniformity of paper-based SERS substrate - Nguyen, Thi Bich Ngoc; Nguyen Trong, Nghia; Nguyen Thi, Thuy; Nguyen Duc, Toan; Nghiem Thi Ha , Lien (Communications in Physics, 2025)
Chitosan, a natural polysaccharide derived from crustacean shells, was employed as a functional additive in the fabrication of paper-based SERS substrates via a direct chemical reduction method. Acting as a binding agent between silver ions and cellulose fibers, chitosan facilitates the formation of positively charged [Ag(Chitosan)]+ complexes through its amino (–NH₂) and hydroxyl (–OH) groups. This interaction significantly enhances the loading and uniform distribution of silver nanostructures on filter paper. In the presence of chitosan, the resulting silver nanostructures exhibit well-defined, bar-like morphologies and are orderly arranged along the cellulose fibers, in contrast to the irregular and dispersed structures formed without chitosan. The influence of chitosan on the optical characteristics and SERS performance of the substrates was systematically investigated. Results demonstrate that chitosan notably improves both the enhancement factor (EF) and the signal uniformity of the paper-based SERS substrates, highlighting its dual role as a structural modulator and stabilizer for silver nanostructure growth.